Cladode shape analysis of Nopalea cochenillifera (forage cactus Giant Sweet clone) using anatomical landmarks - Lucena, L. R. R.; Leite, M. L. V. M.; Simões, V. J. L. P.; Izidro, J. L. P. S.; Simplício, J. B. (Cuban Journal of Agricultural Science, 2019)
Cactus has high potential as alternative forage in semi-arid regions, due to their great capacity for phytomass production, large water reserves and ease of propagation. For most plants, one of the key factors of biomass production is leaf area, as this determines the capacity for absorption and use of solar radiation in the photosynthetic process. In the forage cactus this function is done instead by cladodes. The objective of this study was to compare the shape of cladodes of Nopalea cochenillifera using anatomical landmarks. The design deployed was randomized blocks with three replicates using the clone of forage cactus, Giant Sweet. To determine the mean shape of cladodes, 174 cladodes were randomly collected, photographed and stored in jpeg image files. The images were marked with 12 anatomic landmarks. Cluster and discriminant and statistical shape analysis were used to evaluate the differences, discriminate and compare groups of cladodes shapes. Grouping method found three cladode groups. For the cladodes, the overall hit rate by discriminant function analysis was 97.7 %. Shape analysis, presented high discriminatory power and can be considered as potential descriptors to identify cladodes order, making it unnecessary to go in the field for this process, economize costs and time. Key words: cacti, multivariate analysis, Nopalea cochenillifera, shape analysis